The Study of Superior Varieties and New Plant Types of Rice on Various Organic Cropping Systems in Tidal Land - Muhammad Safi'e; Hilda Susanti; Dewi Erika Adriani (Center for Journal Management and Publication, 2022)
Â Increasing rice production with the use of high-yielding varieties and proper plant spacing must consider the environmental aspect. Organic agriculture is an effort to accelerate the cultivation techniques with environmental health, in addition, the research site is a tidal land that has been cultivating rice organically since 2009. The research aimed to study the growth and yield of superior varieties and new plant type of rice on various cropping systems in tidal land. The research was carried out at the Laboratory of Center for Protection of Food Crops and Horticulture, Sungai Tabuk District, Banjar Regency. The experimental design was a split-plot with three replications.Â The main plot were s1 = Tile System, s2 = Legowo System 2:1, s3 = Legowo System 8:1 cropping systems and subplots wereÂ v1= Ciherang, v2= Mekongga, v3= IPB Batola 6R, v4= IPB 3S varieties. The experimental unit was a plot with a size of 10 m2. The results showed that there was no interaction between cropping systems and rice varieties. The main plot of cropping system Legowo 2:1 showed the best percentage of filled grain per panicle (87%). Sub-plot of rice varieties affected some plant growth and yield variables. Superior varieties Ciherang and Mekongga had more tillers and panicles per clump. The new plant type varieties showed a greater number of grains per panicle and tended to have a better percentage of filled grains per panicle and a weight of 1,000 grains.